Conversor CC-CC trifásico isolado bidirecional com comutação suave utilizando dual phase-shift e razão cíclica variável - Oliveira Filho, Hermínio Miguel de (2015)
This work presents the analysis, design example, simulations and experimental results on a soft-switching bidirectional isolated three-phase dc-dc converter using dual phase-shift control with variable duty cycle. The topology uses three single H-bridges in the primary side and a three-phase inverter in the secondary side. High-frequency isolation is ensured by using three single-phase transformers connected in open delta-wye configuration. The variation of both phase-shift (PS) angles between the H-bridge legs and/or primary and secondary sides allows controlling the power flow, while reduced reactive power flow is possible. The variable duty cycle is used to ensure a constant voltage bus and/or zero voltage switching (ZVS) operation. A detailed analysis is presented considering a model based on the fundamental components for the voltages and currents in the transformer and, aiming its validation, a second analysis from the operation stages of the converter has also been developed. Besides, the dynamic model of the converter, based on fundamental components and employing the gyrator theory has been developed. A design example with nominal values assumptions, stresses and specifications for components, discrete control system characterization and its FPGA programming are presented. Simulation and experimental results in steady state and closed-loop performance are presented and discussed to validate the proposed approach.